PEMANFAATAN GRACILARIA SP. SEBAGAI KOMODITAS UNGGULAN DI DESA KUPANG SEBAGAI DAERAH DEVISA RUMPUT LAUT - Rohma, Sofia Ainur; Jiwanti, Nia Soka; Zahra, Nafiesa; Nurhaliza, Yunita Dwi; Herawati, Jenny Dwi; Habiburrochman, Habiburrochman (LPPM Institut Pendidikan Nusantara Global, 2024)
The foreign trade or export sector has a significant impact on Indonesia's economic growth, especially East Java. One of the regencies that is considered to have contributed to increasing exports is Sidoarjo Regency with quite large potential for Gracilaria products. Based on the main issues and opportunities of Sidoarjo district, the research team focused on economic empowerment which was actualized through the Entrepreneurial Village action in the PPK Ormawa program. Based on the issues discovered by the people of Kupang Village, Jabon District, the PPK Ormawa UKM Penalaran team created various innovations in processed food products. The food products have high quality, high marketability, and compete on the market. The products are healthy noodles and meatballs. This has been realized through the